2021
DOI: 10.1021/acs.jctc.0c01002
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the CL&Pol Polarizable Force Field to Electrolytes, Protic Ionic Liquids, and Deep Eutectic Solvents

Abstract: is extended to electrolytes, protic ionic liquids, deep eutectic solvents, and glycols. These systems are problematic in polarizable simulations because they contain either small, highly charged ions or strong hydrogen bonds, which cause trajectory instabilities due to the pull exerted on the induced dipoles. We use a Tang-Toennies function to dampen, or smear, the interactions between charges and induced dipole at short range involving small, highly charged atoms (such as hydrogen or lithium), thus preventing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
126
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(131 citation statements)
references
References 74 publications
5
126
0
Order By: Relevance
“…[195][196][197][198][199] The vast number of possible ionic liquids is yet another serious challenge for force eld development, and transferable force elds are required to not be limited to one particular system. 195,[200][201][202][203][204][205][206][207] Molecular dynamics simulations can be used to predict a wide range of properties of ionic liquids from thermal transitions to transport, structural, or spectroscopic properties. 74,199,[208][209][210][211][212][213][214][215][216] The prediction of properties with MD simulations has two facets.…”
Section: Machine Learning For Molecular Dynamics Simulationsmentioning
confidence: 99%
“…[195][196][197][198][199] The vast number of possible ionic liquids is yet another serious challenge for force eld development, and transferable force elds are required to not be limited to one particular system. 195,[200][201][202][203][204][205][206][207] Molecular dynamics simulations can be used to predict a wide range of properties of ionic liquids from thermal transitions to transport, structural, or spectroscopic properties. 74,199,[208][209][210][211][212][213][214][215][216] The prediction of properties with MD simulations has two facets.…”
Section: Machine Learning For Molecular Dynamics Simulationsmentioning
confidence: 99%
“…The CL&Pol model 71,73,74 presented in this review is built according to a different strategy, favouring generality and transferability. It was developed from the existing fixed-charge CL&P model, 7,13 one of the most widely used for ILs, that had been parameterized following the philosophy and functional form of OPLS-AA (and it is also compatible with AMBER/GAFF).…”
Section: Representing Polarization Explicitlymentioning
confidence: 99%
“…[59][60][61][62] It was recently shown that heat flow to the cold Drude DOFs may lead to unbalanced temperatures between intramolecular and translational center-of-mass DOF. 82 To correct this bias, a triple temperature-grouped Nosé-Hoover thermostat has been implemented in the OpenMM 82 and LAMMPS 74 codes. This improved thermostating scheme provides more accurate dynamic and structural quantities.…”
Section: Drude Induced Dipolesmentioning
confidence: 99%
See 2 more Smart Citations